K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(A=\dfrac{x^4-\left(x-1\right)^2}{\left(x^2+1\right)^2-x^2}+\dfrac{x^2-\left(x^2-1\right)^2}{x^2\left(x+1\right)^2-1}+\dfrac{x^2\left(x-1\right)^2-1}{x^4-\left(x+1\right)^2}\)

\(=\dfrac{\left(x^2-x+1\right)\left(x^2+x-1\right)}{\left(x^2+1-x\right)\left(x^2+1+x\right)}+\dfrac{\left(x-x^2+1\right)\left(x+x^2-1\right)}{\left(x^2+x-1\right)\left(x^2+x+1\right)}+\dfrac{\left(x^2-x-1\right)\left(x^2-x+1\right)}{\left(x^2-x-1\right)\left(x^2+x+1\right)}\)

\(=\dfrac{x^2+x-1}{x^2+x+1}+\dfrac{-x^2+x+1}{x^2+x+1}+\dfrac{x^2-x+1}{x^2+x+1}\)

\(=\dfrac{x^2+x-1-x^2+x+1+x^2-x+1}{x^2+x+1}\)

\(=\dfrac{x^2+x+1}{x^2+x+1}=1\)

ĐKXĐ : \(\hept{\begin{cases}x-2\ne0\\3-4x\ne0\end{cases}\Rightarrow\hept{\begin{cases}x\ne2\\x\ne\frac{3}{4}\end{cases}}}\)

\(\frac{5}{x-2}+\frac{6}{3-4x}=0\)

\(\frac{5\left(3-4x\right)}{\left(x-2\right)\left(3-4x\right)}+\frac{6\left(x-2\right)}{\left(3-4x\right)\left(x-2\right)}=0\)

\(15-20x+6x-12=0\)

\(3-14x=0\Leftrightarrow14x=3\Leftrightarrow x=\frac{3}{14}\)theo ĐKXĐ : x thỏa mãn 

28 tháng 2 2020
https://i.imgur.com/V92CPVX.jpg
28 tháng 2 2020
https://i.imgur.com/yXrzVbQ.jpg